Critical power concept adapted for the specific table tennis test: Comparisons between exhaustion criteria, mathematical modeling, and correlation with gas exchange parameters - Zagatto, A.; Miranda, M. F.; Gobatto, C. A. (International Journal of Sports Medicine, 2011)
The purposes of this study were to determine and to compare the critical power concept adapted for the specific table tennis test (critical frequency - Cf ) estimated from 5 mathematical models and using 2 different exhaustion criteria (voluntary and technical exhaustions). Also, it was an aim to assess the relationship between Cf estimated from mathematical models and respiratory compensation point (RCP), peak oxygen uptake (VO2PEAK) and minimal intensity at which VO2PEAK (f VO2PEAK) appears. 9 male table tennis players [18(1) years; 62.3(4.4) kg] performed the maximal incremental test and 3-4 exhaustive exercise bouts to estimate Cf s (balls · min-1). The exhaustion time and Cf obtained were independent of the exhaustion criteria. The Cf from 3-parameter model [45.2(7.0)-voluntary, 43.2(5.6)-technical] was lower than Cf estimated by linear 2-parameter models, frequency-time-1 [53.5(3.6)-voluntary, 53.5(3.5)-technical] and total ball thrown-time [52.2(3.5)-voluntary, 52.2(3.5)-technical] but significantly correlated. Cf values from 2 linear models were significantly correlated with RCP [47.4(3.4) balls · min-1], and Cf values of the linear and nonlinear models were correlated with f VO2PEAK [56.7(3.4) balls · min-1]. However, there were no significant correlations between Cf values and VO2PEAK [49.8(1.1)ml · kg-1 · min-1]. The results were not modified by exhaustion criteria. The 2 linear and non-linear 2-parameter models can be used to estimate aerobic endurance in specific table tennis tests.